A GENRE-BASED APPROACH IN TEACHING MULTIMODAL TEXTS - Nugraha, Irsyad; Emilia, Emi; Gunawan, Wawan (English Review: Journal of English Education, 2024)
Abstract: This research aims to investigate how the teaching and learning processes of English Education Program Students occur in creating multimodal texts using the Genre Based Approach teaching method. The study seeks to demonstrate that Genre Based Approach, as a teaching method for academic reading and writing courses, can assist students in creating their own multimodal texts, which combine words and images. Participatory Case Study is employed as the research design, aiming to delve deeper into the phenomenon of teaching and learning processes within it. The use of field notes in each phase of the learning activities is crucial in this research as it clearly records interactions between lecturers and students in the classroom. This study provides evidence that the analysis based on the Image Framework analysis (O'Halloran, 2008) in collaboration with the Transitivity System from Systemic Functional Linguistics (Emilia, 2014) enables students to comprehend multimodal texts, analyze them, and ultimately create their own multimodal texts using the genre of analytical exposition. The results of this research demonstrate that the Genre Based Approach teaching process, conducted over 14 sessions from February 21 to April 10, 2024, has improved the reading and writing abilities of fourth-semester students who will be undertaking the PLP program in their fifth semester. This improvement is evidenced by the pre-test and post-test results, which measured understanding of multimodal texts and the production of multimodal texts.